Psychological Insulin Resistance (PIR) Among Type 2 Diabetes Patients at Public Health Clinics in Federal Territory of Malaysia - Z, Nur Azmiah; AK, Zulkarnain; A, Tahir (IIUM Medical Journal Malaysia, 2011)
Introduction: Insulin has been viewed as a treatment option of last resort in type 2 diabetes management. The decision to start insulin therapy is often diffi cult. Patients are usually reluctant to begin insulin and many cases delay the initiation of insulin therapy. The aim of this study is to determine the magnitude of insulin refusal or recognize as psychological insulin resistance (PIR) and to identify its predictors. Materials and Methods: This is a cross-sectional study and data was collected from two primary public health clinics in Kuala Lumpur and Putrajaya. The study sample consisted of 404 insulin naive patients with type 2 diabetes. A self-administered questionnaire was used to obtain demographic and clinical information. Results: Fifty-one percent of patients with type 2 diabetes were found to be unwilling to take insulin. Regression analysis revealed that females were 2.7 times more likely to resist insulin treatment compared to males and those with uncontrolled diabetes were 1.8 times more likely to resist insulin treatment compared to controlled diabetics. Patients will refuse insulin if they perceived their diabetes worsen with insulin use. After controlling for other attitudinal belief factors in the model, an increase in one unit of perceived disease severity will increase the likelihood of PIR around 2 times. Conclusion: Several misconceptions regarding insulin therapy were identifi ed and specifi c education intervention is recommended for successful transition to insulin therapy.